Voltage gated ion channels blockade is the underlying mechanism of BIMU8 induced cardiotoxicity. (5th August 2017) - Iqbal, Shahid Muhammad; Lemmens-Gruber, Rosa
Highlights: BIMU8 blocks cardiac hERG ion channels. BIMU8 blocks cardiac NaV 1.5 ion channels. BIMU8 blocks cardiac CaV 1.2 ion channels. Abstract: BIMU8 is a 5-HT4a receptor agonist and used as an experimental drug to counteract opioid induced respiratory depression. In preliminary experiments serious disturbances in ECG were observed in anesthetized rabbits which prompted us to explore the underlying cause of BIMU8 induced abnormal changes in ECG recordings. Electrophysiological experiments were performed on HEK-293 cells expressing hERG, CaV 1.2 and NaV 1.5 ion channels. In whole-cell recordings BIMU8 effectively blocked these three channels, with IC50 values of 0.06 ± 0.05, 1.46 ± 0.26 and 4.66 ± 0.58 μM for hERG, NaV 1.5 and CaV 1.2, respectively. Additionally it also produced a hyperpolarizing shift of 3.27 mV in half maximal activation and 12.87 mV in fast inactivation of NaV 1.5 channel. These experimental findings indicate that BIMU8 is a potent blocker of hERG, NaV 1.5 and CaV 1.2 cardiac ion channels thus revealing its proarrhythmic potential.